Determinations of The Depths to Magnetic Sources Over Al-Ma′Aniyah Depression Area-Southwest Iraq Using The Aeromagnetic Data and Their Tectonic Implication - Abdulrahim, Hussein; Al-Rahim, Ali M. (Iraqi Journal of Science, 2019)
Tectonically, the location of the Al-Ma’aniyah depression area is far from active boundary zones, their tectonic features have to reflect the original depositional environments with some horizontal movement due to rearrangement of the basement blocks during different actives orogenic movements. So, the analysis of aeromagnetic data were considered to estimate the thickness and structural pattern of the sedimentary cover sequences for this area. The aeromagnetic data, which are derived from Iraqi GEOSURV to Al-Ma′aniyah region is analyzed and processed for qualitative and quantitative interpretations. The process includes reducing the aeromagnetic data to pole RTP, separation the aeromagnetic data to regional and residual using power spectrum techniques and derivatives methods to delineate the anomalies boundary. The delineated anomalies from magnetic data are dependent for quantitative interpretation using 3D forward and inverse modeling. The depths of magnetic sources are 7-8 km at north and northeastern parts of study area and is about 8-10 km at south and southwestern parts of study area.